Albania : Technical Assistance Report-Revenue Administration: Supporting the Delivery of the Reform Agenda. (IMF Staff Country Reports; Country Report, 2019)
This Technical Assistance Report discusses several tax administration issues and high-level recommendations for the reform agenda. The General Directorate of Taxes (GDT) continues to make good progress in modernizing its administration of the taxation system. A program to consolidate some core functions into fewer regional locations, beginning with the arrears collection function, should be accelerated. The GDT's increased use of electronic services and telephone contact centers reduces the need for face-to-face contact with taxpayers. The GDT must have access to a broader range of third-party information, and data-warehouse facilities to manage the risk assessment with automated analytical tools. There are some positive developments in the audit function; however, further capacity building is necessary. A new comprehensive desk audit manual has been developed, which will help to standardize operations and provide more appropriate case allocation based on auditor experience and skills.